Heat Transfer Analysis and Friction Factor of Ternary Nanofluids with Twisted Tape Inserts - Ramadhan, Anwar Ilmar; Azmi, Wan Hamzah; Lasman, As Natio; Umar, Efrizon; Sharma, Korada Viswanatha (Indonesian Journal of Computing, Engineering, and Design (IJoCED), 2024)
This study investigates the heat transfer efficiency and friction factor of ternary nanofluids (Al₂O₃-TiO₂-SiO₂) in a simple tube equipped with a twisted tape. Ternary nanofluids, prepared using a volume-based composition ratio of 20:16:64, were tested at various volume concentrations ranging from 0.5% to 3.0%. Forced convection heat transfer experiments were conducted under varying Reynolds numbers (2,300 to 12,000) and a bulk temperature of 70 °C. The results indicate that the maximum viscosity occurs at a volume concentration of 3.0%. The highest increase in heat transfer for ternary nanofluids in a simple tube with twisted tape (H/D = 2.0) was achieved at a volume concentration of 3.0%, reaching 225.35%. Compared to a plain tube, the average thermal performance factor (TPF) of the twisted tape was significantly improved, with a further increase observed when the volume concentration rose from 2.73% to 3.22%.